1996
DOI: 10.1111/j.1745-4573.1996.tb00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Microbial and Sensory Changes in Ice‐stored Sea Scallops (Placopecten Magellanicus) Treated With Sodium Tripolyphosphate

Abstract: Sea scallop adductor muscles were given six processing treatments involving water, phosphate and NaCl. They were evaluated during iced storage for changes in moisture content, aerobic plate count, pH, drip loss, cook loss, and sensory freshness attributes. All treated scallops and a wash control were above the 80% moisture interim federal compliance level. A dip in 10% sodium tripolyphosphate generally produced the least drip and cook losses and lowest aerobic plate counts during iced storage compared to fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…1 and Table 1 demonstrate relatively small drip losses after cooking for shrimps treated with phosphate, which confirms the ability of phosphates in retaining moisture. These data are also in agreement with studies of Rippen et al (1993), Ü nal, Erdogdu, Ekiz, and Ozdemir (2004) and Gonçalves et al (2008), which showed that polyphosphates control loss of natural juices during thawing and cooking processes, by increasing water holding capacity.…”
Section: Drip Loss Evaluation On Thawing and After Cookingsupporting
confidence: 94%
“…1 and Table 1 demonstrate relatively small drip losses after cooking for shrimps treated with phosphate, which confirms the ability of phosphates in retaining moisture. These data are also in agreement with studies of Rippen et al (1993), Ü nal, Erdogdu, Ekiz, and Ozdemir (2004) and Gonçalves et al (2008), which showed that polyphosphates control loss of natural juices during thawing and cooking processes, by increasing water holding capacity.…”
Section: Drip Loss Evaluation On Thawing and After Cookingsupporting
confidence: 94%
“…The addition of phosphates has been shown to improve water-holding capacity of the product ( 21 ). Although much work has been conducted on the effects of polyphosphate treatment on food products including meat and seafood, the actual mechanism of the action of polyphosphates on proteins is not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations for the composition of processed scallops derived from moisture contents <80% [39,40] and a moisture/protein (M/P) ratio ≤5.0 [3,5]. All fresh samples fulfilled these guidelines.…”
Section: Resultsmentioning
confidence: 99%